Genes related to flooding tolerance during germination and early growth of weedy rice. (10th November 2020) - Kaspary, Tiago Edu; Cutti, Luan; Rafaeli, Rafael Schwalm; Delatorre, Carla Andrea; Merotto, Aldo
Abstract: Evolution of flooding tolerance in weedy rice has occurred in several rice‐growing regions, but the genes related to this process and the environmental effects are unknown. The objective of this study was to analyse the expression of genes related to flooding tolerance in response to temperature and flooding during the initial establishment of weedy rice. The experiments were carried out with rice cultivars IRGA 417 and Nipponbare, which are sensitive to flooding, and weedy rice ITJ03 and AV04 genotypes that have high and intermediate tolerance to flooding, respectively. The expression of genes related to reserve mobilisation, anaerobic respiration, escape and quiescence strategies was analysed at periods up to 24 days after sowing. The flooding tolerance of weedy rice genotype ITJ03 was associated with the expression of RAmy3D and OsTPP7, which are involved in the mobilisation of carbohydrate reserves, ADH1 and ADH2, which participate in anaerobic respiration, and SNRKL1 that triggers rapid elongation of the coleoptile and emergence. Although the genes PDC1, SUS3 and SUB1 are important for flooding tolerance in cultivated rice, their expression was not directly related to flooding tolerance in weedy rice. A temperature of 20°C reduced levels of expression of the RAmy3D, ADH2 and SNRKL1 genes and low temperature had a negative effect on the establishment of weedy rice. Breeding of rice genotypes with tolerance of low temperatures and anaerobic conditions may be a viable strategy to improve the control of weedy rice in paddy fields.